2013
DOI: 10.2142/biophysics.9.63
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Dc domain of the bacterial hook protein FlgE in hook assembly and function

Abstract: The bacterial flagellar hook acts as a universal joint to smoothly transmit torque produced by the motor to the filament. The hook protein FlgE assembles into a 55 nm tubular structure with the help of the hook cap (FlgD). FlgE consists of four domains, D0, Dc, D1 and D2, arranged from the inner to the outer part of the tubular structure of the hook. The Dc domain contributes to the structural stability of the hook, but it is unclear how this Dc domain is responsible for the universal joint mechanism. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…4A, lower panel). These results are in agreement with the findings of Kornacker and Newton (1994) and Moriya et al . (2013) who showed in a deletion analysis of FlgE that a region comprising residues 30–58 is important for export of FlgE.…”
Section: Resultssupporting
confidence: 94%
“…4A, lower panel). These results are in agreement with the findings of Kornacker and Newton (1994) and Moriya et al . (2013) who showed in a deletion analysis of FlgE that a region comprising residues 30–58 is important for export of FlgE.…”
Section: Resultssupporting
confidence: 94%
“…Residues Gly 329 -Asp 330 of subunit 0 at the tip of a short β-hairpin of domain D1 interact with residues Ala 39 -Asp 40 of subunit 5 in the distal part of the long β-hairpin of domain Dc, and this interaction does not change by protofilament compression and extension (Fig. 3d), indicating the importance of the long β-hairpin of domain Dc for the structural stability of the hook as found by deletion mutation experiments 13 .…”
mentioning
confidence: 62%
“…It has been shown that the Dc domain of FlgE affects the hook supercoiling27. To investigate how the GSS insertion affects the morphology of the hook and its mechanical property, we isolated the flagellar hook-basal bodies from the wild-type and flgE + GSS mutant cells (Fig.…”
Section: Resultsmentioning
confidence: 99%